The Early Years Home Learning Environment – Associations With Parent-Child-Course Attendance and Children’s Vocabulary at Age 3 - Linberg, Anja; Lehrl, Simone; Weinert, Sabine (Frontiers in Psychology, 2020)
Although many studies investigated the effects of the home learning environment (HLE) in the preschool years, the constructs that underlie the HLE in the years before the age of three and its effects on language development are still poorly understood. This study therefore investigated the dimensionality of the home learning environment at age two, its relation to the attendance of low threshold parent-child-courses, and its importance for children’s vocabulary development between age two and three years against the background of differing family background characteristics. Using data from 1013 children and their families of the Newborn Cohort of the German National Educational Panel Study, structural equation modelling analyses showed that (1) quantitative and qualitative aspects of the early HLE, i.e. the frequency of stimulating activities, and the quality of parent-child-interactions should be differentiated; (2) that family background variables are differentially associated with the HLE dimensions and (3) that attendance at parent-child courses enriches both aspects of the HLE which in turn (4) are related to the children’s vocabulary development. Our results highlight the need to differentiate aspects of the early HLE to disentangle which children are at risk in terms of which stimulation at home and the possibility to enrich the HLE through low threshold parent-child courses.